2012
DOI: 10.1242/jcs.092825
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dynamic actin associations with T-cell receptor microclusters in primary T cells

Abstract: SummaryT cell triggering through T-cell antigen receptors (TCRs) results in spatial assembly of the receptors on multiple length scales. This assembly is mediated by the T cell actin cytoskeleton, which reorganizes in response to TCR phosphorylation and then induces the coalescence of TCRs into microclusters, followed by their unification into a micrometer-scale structure. The exact outcomes of the association of TCRs with a dynamic and fluctuating actin network across these length scales are not well characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…This suggests that the coupling between microclusters and actin is rather transientmultiple weak links form and break at different times to generate a frictional force between microclusters and actin. Two subsequent studies provided further support for the idea of the frictional coupling model and showed that actin itself slows down as it passes over mechanically trapped TCRs (Yu et al, 2010;Smoligovets et al, 2012).…”
Section: Actin In Microcluster Translocation and Spatial Organizationmentioning
confidence: 85%
“…This suggests that the coupling between microclusters and actin is rather transientmultiple weak links form and break at different times to generate a frictional force between microclusters and actin. Two subsequent studies provided further support for the idea of the frictional coupling model and showed that actin itself slows down as it passes over mechanically trapped TCRs (Yu et al, 2010;Smoligovets et al, 2012).…”
Section: Actin In Microcluster Translocation and Spatial Organizationmentioning
confidence: 85%
“…1, 2, and 4), suggesting weaker interactions between these assemblies and the cell cytoskeleton. Studies following retrograde flow in the IS support this scenario, as the speed of TCR microcluster transport on supported lipid bilayers is about half the actin flow speed, and restriction of microcluster transport slows but does not stop actin retrograde flow (39)(40)(41). Moreover, immobilization of integrin receptors within the IS slows actin transport to a larger degree than TCR microclusters (39).…”
Section: Discussionmentioning
confidence: 99%
“…Nanopatterned substrates have been successfully employed to elucidate the role of receptor clustering in a number of cellular signaling systems, including T-cell activation, EphA2 receptor tyrosine kinase signaling, and integrin adhesion (24)(25)(26)(60)(61)(62)(63)(64)(65)(66). Unlike genetic or pharmacological perturbations that may have offtarget or deleterious effects (e.g., on protein stability), these nanopatterned substrates allow receptor clustering to be perturbed in a purely physical way, thereby avoiding such effects.…”
Section: Discussionmentioning
confidence: 99%